Numerical Calculation of Solid-Liquid Two-Phase Flow in Open-Design Vortex Pump. Issue 1 (1st August 2022) - Gao, Xiongfa; Shi, Weidong; Wang, Junhua; Lu, Hongzhong; Wang, Jiabin; Meng, Wanli; Jin, Jiamin
Abstract: This paper mainly based on the CFD platform, numerical simulation of the internal flow field in the open-design vortex pump under different solid particle concentration and particle size is carried out to explore the flow trajectory characteristics of solid particles in the impeller channel and the lateral cavity, as well as the distribution characteristics of solid particles, and calculate the sliding velocity of particles in the impeller channel. The results show that at different solid particle concentrations, the solid volume fraction f in the front and rear cover plate area of the blade is high and that in the middle area is low; The solid volume fraction f decreases gradually from the working face to the back, and the solid particles are widely distributed in the inlet area. Due to the asymmetry of the volute structure, the particle concentration in the inlet area corresponding to the casing tongue is significantly higher than that in other areas; Due to the existence of circulating flow and through flow, the solid particles are distributed in a circular direction in the lateral cavity, and the particle concentration in the middle region is large; In the impeller area corresponding to the casing tongue, the sliding velocity of solid particles decreases with the increase of particle size, and the sliding velocity values of 0.5mm and 1.0mm particle sizes are close.